CNT-reinforced iron and titanium nanocomposites: Strength and deformation mechanisms. (15th April 2020) - Faria, Bruno; Guarda, Cátia; Silvestre, Nuno; Lopes, José N. Canongia
Abstract: The mechanical reinforcement of embedding a carbon nanotube inside metals with different crystal structures (BCC-Fe and HCP-Ti) is investigated using molecular dynamics simulations. Two metallic elements were chosen representing different crystal structures, based on the foreseeable technological benefits of improving the strength of these widely used metals while reducing their weight. Tensile and compressive loadings are applied to CNT-Fe and CNT-Ti nanocomposites which are modeled by inserting a (6, 6) CNT into a single-crystal rectangular prism. Two limit boundary conditions are applied to the embedded CNT: (i) loading applied only to the metal matrix and (ii) loading applied to both the metal matrix and the embedded CNT. Curves of energy vs strain and stress vs strain are presented and the mechanical properties are calculated for both situations. Additionally, the mechanical behavior and buckling of the encapsulated carbon nanotube as a result of compression loading applied to the metal nanocomposites is also studied. Lastly, an analysis of the influence of the embedded CNT in the deformation mechanisms of the nanocomposites is presented.